The Cosmology of Tana Toa: Local Knowledge, Traditions, and Experiences of Forest Preservation in South Sulawesi, Indonesia - SABRI, Muhammad; SALAHUDDIN, Muh.; NUNSI, Lanri Febrianty M; DATU, Nurcholish Madjid (Journal of Environmental Management and Tourism; Vol 14 No 3 (2023): JEMT, Volume XIV, Issue 3(67), Summer 2023DO - 10.14505//jemt.14.3(67).15, 2023)
The study aims to explore the traditions of the Kajang people in nature/forest management based on their local knowledge and experience. In specific, this research describes the concept of cosmology of the Kajang tribe and the nature management system based on the prevalent social system in the Kajang tribe community. The research methods used in the study were interviews, observations, and documentation. Key leaders in the Kajang tribe community were the primary sources in this research. The collected data were analyzed and validated through focused group discussion sessions, discussions with peers, and discussions with experts. In this study, it was discovered that the Kajang people believe that nature comes from God and sent someone from the sky to lead the Kajang people with the aim of protecting and preserving nature. Pasang Ri Kajang is a spiritual message passed down through oral tradition to preserve nature in the Kajang community system.